2017
DOI: 10.3102/0013189x17737739
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Early Childhood Education on Medium- and Long-Term Educational Outcomes

Abstract: Despite calls to expand early childhood education (ECE) in the United States, questions remain regarding its medium- and long-term impacts on educational outcomes. We use meta-analysis of 22 high-quality experimental and quasi-experimental studies conducted between 1960 and 2016 to find that on average, participation in ECE leads to statistically significant reductions in special education placement (d = 0.33 SD, 8.1 percentage points) and grade retention (d = 0.26 SD, 8.3 percentage points) and increases in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
130
1
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 41 publications
(44 reference statements)
2
130
1
9
Order By: Relevance
“…At this juncture, it remains unclear which of these theories best describes patterns in the empirical evidence base. Empirically, in the medium term, the older evidence has shown that preschool has small‐to‐moderate effects in reducing grade retention and special education placement in the K‐12 years (McCoy et al, ; Yoshikawa, Weiland, & Brooks‐Gunn, ). In both older and more recent studies, language, literacy, and mathematics test scores between preschool participants and nonparticipants tend to partially or fully converge by the end of third grade, though some studies do show some evidence of medium‐term persistence (e.g., Bassok, Gibbs, & Latham, ; Hill, Gormley, & Adelstein, ; Ladd, Muschkin, & Dodge, ; Lipsey, Farran, & Durkin, ; Phillips et al, ; Puma et al, ).…”
Section: When Might Prekindergarten Benefits Persist?mentioning
confidence: 99%
“…At this juncture, it remains unclear which of these theories best describes patterns in the empirical evidence base. Empirically, in the medium term, the older evidence has shown that preschool has small‐to‐moderate effects in reducing grade retention and special education placement in the K‐12 years (McCoy et al, ; Yoshikawa, Weiland, & Brooks‐Gunn, ). In both older and more recent studies, language, literacy, and mathematics test scores between preschool participants and nonparticipants tend to partially or fully converge by the end of third grade, though some studies do show some evidence of medium‐term persistence (e.g., Bassok, Gibbs, & Latham, ; Hill, Gormley, & Adelstein, ; Ladd, Muschkin, & Dodge, ; Lipsey, Farran, & Durkin, ; Phillips et al, ; Puma et al, ).…”
Section: When Might Prekindergarten Benefits Persist?mentioning
confidence: 99%
“…From birth to 5 years is an important developmental period in which children rapidly develop significant language, cognitive, and social-emotional skills that predict later functioning at school and into adulthood (McCoy et al 2017). It is, therefore, important to provide relevant learning supports for young children who Control, M (n = 20) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While many technologies have emerged to support youth in exploring computational concepts and practices, opportunities in early childhood are especially promising to cultivate interests early in computing as well as to support the development of social, emotional, and cognitive milestones [3,9]. Many studies have shown that early interventions can have compounding effects later in life and influence personal and academic outcomes [33]. Early exposure can also help mitigate barriers to participation in computing.…”
Section: Introductionmentioning
confidence: 99%